Tata Steel’s Corporate Social Responsibility Policy and its Impact on Tata’s Expansion and Business Decisions - Das, Gaurav (2015)
Corporate Social Responsibility is an integral part of any company. Corporate Social responsibility refers to the companies taking responsibility for the impact that their strategies have on the society around them. As recent studies have shown, CSR has a major impact on the competitiveness and long term success of a company. CSR is a kind of regulatory mechanism for many companies through which they gauge the impact that their business decisions have on the local communities. CSR is basically the moral and ethical responsibilities which the companies have towards the local communities in which the companies flourish. Now, there are many supporters of CSR, who invariably say that incorporating CSR into the company’s long term strategies leads to higher profits and make the company seem as people friendly. The critics, on the other hand, have maintained that CSR does nothing other than detract from the main objective of making an economic profit. The critics view CSR as basically a Band-Aid over the wounds inflicted by the operations of the companies. Many critics also argue that companies introduce a CSR policy just to avert the gaze of government watchdogs on their operations and to paper over the cracks caused in the local community by the actions of powerful MNC’s. So which view is actually correct? I attempt to answer this question by studying the Corporate Social Responsibility policy of the TATA Sons. The TATA’s are one of the world’s biggest conglomerates with their interests ranging from manufacturing steel to running airlines and providing telecommunication services and building cars and houses. It is one of the most diversified MNC’s in existence today. That is why I have chosen to study their CSR policy so that I can get an idea of exactly what CSR means to a truly global organization. The main question which I’ll be attempting to answer is “What impact does Corporate Social Responsibility have on the strategies of a global company.” Does TATA have different CSR policies for different countries or does it have the same core values across borders? What impact does it have on the local population? Does its CSR policy actually help the TATA group make a better impression and leads to higher profits? These are the questions which I attempt to answer through my research. For example, Tata Steel has established a number of townships around its offices. The most famous example being the Steel City of Jamshedpur which is basically run entirely by the TATA Group. The roads are maintained by the TATA’s. The electricity is provided by them. In fact out of the population of over 5 million people, 70 % are Tata employees. But is such a strategy viable in another country, say for example the United Kingdom? Will the UK government allow an MNC to run a whole township? And what impact will the local population have on the decisions? Will such a policy be successful when there is a lack of natural resources and the costs of running such a town will incur losses for the Tata Group? In essence, I will be interviewing the Managing Director of Tata Steel and the Chief of Human Resources of the Tata Group and their subordinates regarding their CSR policy. I will attempt to answer the questions outlined above and try and get a picture of the impact that CSR has on the internationalization strategies of truly global organizations like the Tata Group.